Cartas: uma possibilidade para o ensino do pensamento fenomenológico - Melo, Fabíola Freire Saraiva de (2008)
This dissertation explores a supervised training experience fulfilled at a São Paulo University psychological course. Parents and tutors wrote their doubts related to childhood and educational process into an urn located at the reception room of the refered institution´s clinic. The work with the students comprised teaching them to answer the questions received through letters (written language), intending to develop a descriptive language without judgments. The aim of this project was to exercise the phenomenological thought based on an opening attitude, in conformity with the phenomenological reduction proposal. Thus, the students could build their own way of comunication, approaching Merleau Ponty´s concept of speaking language. The dialogue by the means of letters became a privileged situation to teach and learn the phenomenological thought. Through letters students have an experience with others that summon and mobilize them to reflection, and during the elaboration process, they exercise phenomenological attitude. The writing process request patience, effort and dedication to make possible the reflection, the maturity and the composing process of the sending letter. The letters provide the opportunity to debate, in the context of school class, the conflicts and situations experienced in life, giving the students the possibility to act, without the necessity of the real meeting between the parents/tutors and them. Thus, it has opened a mighty space of learning: formation and experience of a new way of looking things. The project was also a space of dialogue between parents/tutors and psychology students, opening the reflection about the questions made by those who participated of it